Pleomorphic adenoma of the salivary glands: a retrospective study of 40 cases. (Mustansiria Dental Journal, 2018)
Forty cases of pleomorphic adenoma( PA) presented in this study were diagnosed in the department of the Oral Pathology, College of Dentistry , Baghdad University covering the period 1982-1992. The tumours were distributed according to age, gender and site of occurrence. Patients ranged in age from 11 to 80 years. The age group 41-50 years was most frequently affected by PA 12 cases (30%) followed by 3rd and 4th decades 9(22.5%) 7(17.5%), respectively .It is evident in this study that PA was more frequently seen in females 24 (60%) than males16 (40%).It was observed from results that the palate was the most common site for occurrence of PA 32(80%), followed by the parotid gland 3(7.5%). Most of the results were comparable to the data of the literatures.